Socio-Economic and Policy Drivers of Forest and Land Rehabilitation Productivity in Papua’s Yahukimo Regency - Lamba, Arung; Urip, Transna Putra (Journal of Cultural Analysis and Social Change, 2025)
This particular study deals with the productivity challenges of Forest and Land Rehabilitation (FLR) programs in Indonesia, focusing on indigenous communities in Papua's Yahukimo Regency. Forest degradation remains a critical national concern, with approximately 96.3 million hectares requiring restoration. Yet the determinants of successful rehabilitation remain poorly understood, particularly in indigenous settings. The study aims to analyze the institutional, economic, policy, and community drivers influencing FLR productivity and to identify the factors with the greatest empirical impact. The research employs a quantitative approach using structural equation modeling (SEM) on data from 250 indigenous household participants involved in community-based rehabilitation projects. The analysis confirms that institutional capacity (β = 0.36, p < 0.001) exerts the strongest positive effect on rehabilitation productivity, followed by economic conditions (β = 0.29, p < 0.01), policy support (β = 0.22, p < 0.05), and funding mechanisms (β = 0.18, p < 0.05). Community characteristics also demonstrate a positive influence (β = 0.12, p < 0.10). Together, these factors explain 68% of the variance in FLR productivity (R² = 0.68). These results indicate that rehabilitation success depends primarily on institutional coordination, economic incentives, and policy consistency rather than funding magnitude alone. The findings contribute to understanding how integrated institutional-policy-economic mechanisms enhance ecological and socioeconomic outcomes in marginalized regions. The practical value of the study lies in providing an evidence-based framework for policymakers to strengthen local institutional capacity, align policy design with community realities, and integrate economic incentives to ensure sustainable FLR implementation.